Synthesis of Furanose Spirooxindoles via 1, 8‐Diazabicyclo[5.4.0]undec‐7‐ene (DBU)‐Catalyzed Aldol Reactions of a Pyruvic Aldehyde Derivative. Issue 4 (18th March 2014) - Zhang, Dongxin; Johnson, Sherida; Cui, Hai‐Lei; Tanaka, Fujie
Abstract Spirooxindoles are important compounds as they are often found in bioactive molecules. Thus, the development of new spirooxindoles and of synthetic routes to spirooxindoles is a great interest to discover new biofunctional molecules and therapeutic leads. We developed a concise method for the synthesis of spirooxindoles bearing a furanose unit. 1, 8‐Diazabicyclo[5.4.0]undec‐7‐ene (DBU) was used for an aldol reaction of a pyruvic aldehyde derivative with isatin; reduction of the ketone group was followed by treatment with acid to generate the spirofuranose unit. A set of furanose spirooxindoles were obtained in good to high yields.